Being a college counselor on today's campus : roles, contributions, and special challenges - Sharkin, Bruce S. (Routledge, 2012)
"This book provides a detailed description and discussion of the many roles and contributions of college counselors on today's campuses. The author draws on twenty years of experience as a college counselor to address such questions as "Who are college counselors?"; "How does one become a college counselor?"; and "What skills are needed to be a college counselor today?" Roles and responsibilities, including counseling, crisis intervention, consultation, outreach, and administrative duties, are discussed in detail and supplemented with both research and case studies. Diversity competencies and special challenges faced by college counselors are also considered. The firsthand knowledge and experience of the author will make this an engaging and accessible book for both those who are already working in college mental health settings and those who wish to enter it"